Telemedicine: A Paradigm Shift in Patient Care and Digital Health - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2025)
The landscape of healthcare is undergoing a profound transformation, driven by rapid advancements in digital technology. At the forefront of this evolution i...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Medical Ethics